O gwarowym wyrazie kalafa ‘rzadkie błoto, maź’ i jego wariantach - Karaś, Halina (Slavia Occidentalis, 2024)
The article discusses the dialect word kalafa meaning ‘running mud, goo’ and its variants kalawa, kolawa, kalowa, chalawa, galafa, also explaining the reasons for the variants. The basic variant has been established and its origin determined. Other meanings of the above dialectal words are also presented, including ‘a puddle after rain’, ‘a pond (usually shallow and muddy)’, ‘liquid manure’. Based on the lexicographical and atlas attestations, their territorial ranges have been determined. Kalafa is a homonymic word, so data on the homonym kalafa ‘muzzle, gob’, pejorative of ‘face’, also ‘nose’, ‘mouth’ are also presented. Reference has been also made to onomastic data, i.e. local names: Kolawa, Kolawy, Kalawa as well as surnames: Kalafa, Kalawa, Kolawa, and surname forms derived from them (e.g. Kalawski, Kolawski, Kalawinski, Kolawczyk). The analysis of dialectal data has also made it possible to put forward a new etymological hypothesis as to the kolawa || kalawa appellative, the Kolawa || Kalawa anthroponym, and the co-native names.